Perancangan Media Pembelajaran Sekolah Dasar Berbasis Android Menggunakan Metode Rekayasa Perangkat Lunak Air Terjun ( Waterfall ) - Dewi Driyani (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2018)
The first and second grades in Elementary School (SD) are the initial levels in formal schools for students in Indonesia. A change from informal schools to formal schools makes students get into difficulty in understanding a good learning process. Technology is an alternative and innovation that can be used to facilitate funnier learning process in order to improve the quality of education. The design of a technology-based learning medium for Elementary School students is expected to improve the learning skill. This learning medium contains exercises that can be practiced by Elementary School students to understand subjects, improve knowledge and enhance their academic ability. The purpose of the research is to create an interactive android-based learning medium for Elementary School students. The method used in this research is Waterfall Software Engineering (Waterfall) which consists of five stages: Requirements (needs analysis), Design (design and modeling), Implementation, Verification and Maintenance. However, it is limited to the implementation stage. The research performed in stages and sequence using of Waterfall method produces the design of android-based learning media for Elementary School that can create funnier learning process, improve knowledge and enhance ability of students to understand subjects.